Automatic scarecrow / Muhamad Azim Wafiq Khairuddin, Wan Aina Fazira Wan Azman and Taufiq Hamdan - Khairuddin, Muhamad Azim Wafiq (2015)
Nowadays, there are many technologies that have been created to make life being more beneficial and practical such as agricultural technology. “Farming” or “agriculture” shall include farming in all of its branches and the cultivation and tillage of the soil, dairying, the production, cultivation, growing and harvesting of any agricultural, aquacultural, floricultural or horticultural commodities, the growing and harvesting of forest products upon forest land, the raising of livestock including horses, the keeping of horses as a commercial enterprise, the keeping and raising of poultry, swine, cattle and other domesticated animals used for food purposes, bees, fur-bearing animals, and any forestry or lumbering operations, performed by a farmer, who is hereby defined as one engaged in agriculture or farming as herein defined, or on a farm as an incident to or in conjunction with such farming operations, including preparations for market, delivery to storage or to market or to carriers for transportation to market. To participate in making life become easier in agriculture, the system created that isa machine called Automatic Scarecrow. Automatic Scarecrow is a project to help reduce the energy of manpower to banishing animals from the farm. By having this machine, the work will be easier and it will also increase the production of the plant because the plant is not being disturbed by the animal anymore and the farmer that using this scarecrow will gain more profit. This project uses PIR motion sensor to act as the ON/OFF switch for all the operation in the machine. The arduino that is used will be programmed to give order to the part of the electronic that is connects to the servo motor. The servo motor is used to rotate the hand of scarecrow 90° each turn.